Association between childhood trauma and risk for obesity: a putative neurocognitive developmental pathway - Luo, Qiang; Zhang, Lingli; Huang, Chu-Chung; Zheng, Yan; Kanen, Jonathan W.; Zhao, Qi; Yao, Ye; Quinlan, Erin B.; Jia, Tianye; Banaschewski, Tobias; Bokde, Arun L. W.; Bromberg, Uli; et al. (BMC medicine, 2020)
Childhood trauma increases the risk for adult obesity through multiple complex pathways, and the neural substrates are yet to be determined.